2007
DOI: 10.1021/bp070087t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synchronization on CD40 Expression and Antibody Production in Hybridoma Cells Stimulated with Anti-mIgG

Abstract: In previous experiments with the 55-6 hybridoma cell line, we showed that cell stimulation with anti-mouse surface immunoglobulin G antibody (anti-mIgG) increased both CD40 expression and specific monoclonal antibody (mAb) production rate. Cell preincubation with lipopolysaccharide (LPS) prior to anti-mIgG stimulation enhanced these results. Moreover, the expression of both CD40 and surface immunoglobulin G (sIgG) were higher for cells in the G1 phase of the cell cycle. Therefore, to determine the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…An increase of the antibody production has been mostly described during the G0 or G1 phase for hybridoma or CHO cells (Becerra, Berrios, Osses, & Altamirano, ; Martin‐Lopez, Garcia‐Camacho, Contreras‐Gomez, & Molina‐Grima, ; Park, Noh, Woo, Kim, & Lee, ; Suzuki & Ollis, ). In contrast to our study, temperature shifts or butyrate treatment were used to arrest the cell cycle in the G1 phase and therefore enrich G0 cells with assumed higher productivity in the stationary phase, in which most of the product is formed (Du et al, ; Hendrick et al, ; Münzer et al, ; Wippermann et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…An increase of the antibody production has been mostly described during the G0 or G1 phase for hybridoma or CHO cells (Becerra, Berrios, Osses, & Altamirano, ; Martin‐Lopez, Garcia‐Camacho, Contreras‐Gomez, & Molina‐Grima, ; Park, Noh, Woo, Kim, & Lee, ; Suzuki & Ollis, ). In contrast to our study, temperature shifts or butyrate treatment were used to arrest the cell cycle in the G1 phase and therefore enrich G0 cells with assumed higher productivity in the stationary phase, in which most of the product is formed (Du et al, ; Hendrick et al, ; Münzer et al, ; Wippermann et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Effect of LPS in Combination with Anti‐Mouse IgG on CD69, CD40, and CD19 Expression. In a previous study (18) we examined activation of the 55‐6 cell line with anti‐mIgG. It was demonstrated that the effect was anti‐mIgG dose‐dependent, and the best results were found at a concentration of 3,700 pg cell −1 .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that concentration of free anti‐mIgG initially added to the culture medium decreased progressively over time due to the capture of anti‐mIgG by secreted IgG2a (18) and at about 60 h was exhausted (Figure 4). The decrease in CD69, CD40, and CD19 expression over time was in agreement with the decrease in free anti‐mIgG concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations